PUERTO RICO The Oldest US Colony & the Newest War (Consortium News, 2025)
Michelle Ellner on the Trump administration's use of Puerto Rico as a launchpad for war on Venezuela. By Michelle Ellner Z-Network When President Donald Trump announced that the C.I.A. had been authorized to conduct operations inside Venezuela, just as U.S drones struck another small boat